The Biblio diet : live long, master metabolism, reduce pain, fight depression, and conquer cancer with healing secrets from the Bible - Rubin, Jordan; Axe, Josh (Worthy Publishing, 2025)
"Nutrition experts Jordan Rubin and Dr. Josh Axe offer a simple and holistic plan for building strength, health, and longevity. Basedon the ancient wisdom of the Bible and confirmed by modern science,The Biblio Diet's ... plan invites you to experience a breakthroughin the health of your entire family by learning to eat and live God's way"--